ANALYSIS OF LECTURER CHARACTERISTICS ON LECTURER PERFORMANCE THROUGH LEARNING EFFECTIVENESS Case Study of Nuku Tidore University - Rosdiana Rosdiana; Tamrin Husaen (Sosiohumaniora, 2022)
This study aims to analyze the results of student evaluations of the performance of lecturers at Nuku University, Tidore Islands City. The population of this research is all faculties in the institution, namely the faculties of economics, maritime affairs, agriculture and forestry, engineering, law, and socio-politics. The research technique used is survey research with quantitative research methods. The sampling technique uses Quota sampling so that the number of samples used is as many as 200 samples spread from 6 faculties using the variables of lecturer characteristics (X1), learning effectiveness (Y1) and lecturer performance (Y2). The analytical tool used in this study is the structural equation modeling (SEM-AMOS) to test the research hypothesis. The results of this study indicate that the variable characteristics of lecturers have no significant effect on lecturer performance, lecturer characteristics have a significant effect on learning effectiveness, learning effectiveness has a significant effect on lecturer performance, and lecturer characteristics have a significant effect on lecturer performance through learning effectiveness.